PENGARUH UKURAN PERUSAHAAN, ASIMETRI INFORMASI, DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2008-2012 - Dian Putri Manulang; Vince Ratnawati; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objectives of the research are to find out empirical evidence of the the effect of company size, information asymmetry, and bonus compensation on earnings management. The sample used in this study were 66 companies listed in Indonesia Stock Exchange during the years 2008 to 2012. Data taken from the Indonesian Capital Market Directory (ICMD) and Financial Statements company. The analysis method of this research using multiple regression. Earning management is measured using discretionary accruals. Company size is measured from the natural logarithm of total asset. Information asymmetry is measured using bid-ask spread. And Bonus compensation is measured using dummy variables, if the company gives bonuses compensation to management is given the value 1 and if not 0. The results of this research show that company size has a significant relationship with earnings management. Information asymmetry doesn't have a significant relationship with earnings management. And bonus compensation doesn't have a significant relationship with earnings management.Keywords: company size, information asymmetry, bonus compensation, earnings management